PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMEN DAN MODEL PEMBELAJARAN KONVENSIONAL PADA KONSEP STRUKTUR ATOM SISWA KELAS X SMA MUHAMMADIYAH 1 PULAU MOROTAI - Milda Abdul Rahman; Zulkifli Zam Zam (Universitas Khairun, 2015)
This research aimed to know the result of the students different by using cooperative learning model the teams’ game tournament type and learning conventional model on the structure atom concept at the tenth year of SMA Muhammadiyah 1 morotai Island. The research used experimental research and design research are pretest posttest control group design. The population of this research at the tenth year of SMA Muhammadiyah 1 morotai island that consist of 38 students’ and that were 2 class were take sample of cluster random sample. The Technique of collecting data of this research were take of essay test and technique of analyzing data using statistic anakova testing. The result of this research showed that there was significant by using cooperative learning model teams’ games tournament. And by using conventional model that were 46%.Key words: Different, TGT, Conventional, The Result of Students Study, The Concept Structure Atom.